Teori Ajaran Cita Hukum (Idee Das Recht) Di Dalam Perlindungan Ekspresi Budaya Tradisional Di Indonesia - Setyawan, Fadjar Ramdhani; Sudarsono, Sudarsono; Yuliati, Yuliati (Fakultas Syariah, 2021)
Abstract:Indonesia is a country that has a pluralistic culture. The original cultural diversity of the Indonesian nation needs to be guaranteed and protected by law that is in line with the ideals of the law. This study aims to describe the legal protection of traditional cultural expressions in Indonesia and their conformity with the teachings of legal ideals (idee das recht). This article is based on doctrinal law research with a statutory approach and a conceptual approach. The results of this study indicate that the teachings of legal ideals require that a regulation must be able to provide guarantees of legal certainty, justice, and expediency. The regulation of the protection of traditional cultural expressions is not in accordance with the teachings of legal ideals. Legal justice cannot be achieved because there is still no clear identification process for the custodian. The government needs to immediately revise Law no. 5 of 2017 concerning the Advancement of Culture.Keywords: cultural expressions; ideals of the law; intellectual property.Abstrak:Indonesia merupakan negara yang memiliki kebudayaan yang majemuk. Ragam kebudayaan asli bangsa Indonesia perlu dijamin dan dilindungi oleh hukum yang selaras dengan cita hukum. Penelitian ini bertujuan mendeksripsikan perlindungan hukum terhadap ekspresi budaya tradisional di Indonesia dan kesesuainnya dengan ajaran cita hukum (idee das recht). Artikel ini berdasarkan penelitian hukum doctrinal dengan pendekatan perundang-undangan dan pendekatan konsep. Hasil penelitian ini menunjukkan bahwa ajaran cita hukum menghendaki suatu peraturan harus mampu memberikan jaminan akan kepastian hukum, keadilan, dan kemanfaatan. Pengaturan perlindungan ekspresi budaya tradisional belum sesuai dengan ajaran cita hukum. Keadilan hukum tidak dapat tercapai dikarenakan masih belum ada proses identifikasi yang jelas terhadap custodian. Pemerintah perlu segera melakukan revisi terhadap Undang-undang No. 5 tahun 2017 tentang Pemajuan Kebudayaan.Kata Kunci: ekspresi budaya; ajaran cita hukum; kekeyaan intelektual. Â